Erratum for: Halal Products Assurance Policy Model and Its Impact on Sustainability of Fish Ball SMI using System Dynamics Simulation Approach - Handayani, Dwi Iryaning; Haryono, Haryono; Prihatiningsih, Tri (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2020)
We apologize for the error in the article "Halal Products Assurance Policy Model and Its Impact on Sustainability of Fish Ball SMI using System Dynamics Simulation Approach". The errors are:The title changed from “Halal Products Assurance Policy Model and Its Impact on Sustainability Fish Ball SMI with Dynamic System Simulation Approach” to “Halal Products Assurance Policy Model and Its Impact on Sustainability of Fish Ball SMI using System Dynamics Simulation Approach”.“dynamic system” changed to “system dynamics” on the entire page.Page 47. Table 1. No 8. “the higher the cost, the better” changed to “the higher, the better”.Original article has been corrected.